Crescimento de cana-de-açúcar sob aplicação de biofertilizante da bovinocultura e ureia - De Mendonça, Henrique Vieira; Ometto, Jean Pierre Henry Balbaud; Da Rocha, Wadson Sebastião Duarte; Martins, Carlos Eugênio; Otenio, Marcelo Henrique [UNESP]; Borges, Cristiano Amancio Vieira (Centro Universitario de Maringa, 2016)
Effluents from intensive cattle breeding and treated with anaerobic reactors are highly relevant for agricultural reuse. Current paper assesses the growth of sugarcane cultivars SP 803280 and RB 867515 for 220 days. Doses 0, 16, 48, 64, 80 and 96 kg ha-1 N were applied derived from biofertilizing sources produced by cattle-breeding waste water and urea. Experimental design comprised randomized blocks with 96 splits and four replications. The cultivars fertilized with biofertilizers caused growth similar to those fertilized with urea. Doses 64, 80 and 96 kg ha-1 had the best efficiency in growth. Since average height of 3 m was obtained for cultures at the end of the experiment, urea may be replaced by biofertilizers.
Sugarcane growth with cattle biofertilizer and urea
Keywords: Biofertirrigation; Cattle wastes; Nitrogen